Pengaruh Penggunaan Jenis Biochar Terhadap Perkecambahan Benih Cendana (Santalum album Linn.) - Umbu Maramba Hawu; Astin E. Mau; Norman P. L. B. Riwu Kaho (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
Sandalwood (Santalum album Linn.) is a wood-producing forest plant in East Nusa Tenggara Province (NTT) that has great economic value and is an endemic species. Sandalwood is one type of plant that has high economic value. Propagation of sandalwood can be done in vegetative and generative ways. Sandalwood propagation until now still relies heavily on generative propagation by utilizing sandalwood seeds as propagation material. One of the alternatives to increase soil fertility is through the use of organic fertilizers, namely Biochar chicken manure and cow manure can overcome Ultisol soil problems as an alternative The application of biochar into the soil can improve the physical, chemical, and biological properties of the soil, namely it can increase porosity, water holding capacity, soil aggregation, increase pH, cation exchange capacity, soil organic carbon, retention and availability of nutrients, and improve the microbial, meso and macro life of soil fauna. This study aims to determine the effect of the use of biochar on the germination of Sandalwood seeds (Santalum album Linn.). The method used in this study was CompletelyRandomzed Design (CRD), with 4 treatments and each treatment was repeated 5 times so that 20 experimental units were obtained. The experimental unit in the form of a mixture of germination media is put into the germination tub. Each sprout tub is planted with 50 seeds, so that a total of 1000 Sandalwood seeds are needed for all treatments and replicates. The results of the study showed that the M2 treatment (3 kg of soil + 2 kg of chicken manure biochar) had a very real effect and was also the best treatment that affected germination power, germination speed index, and germination value.